Ceramic material for packaging structure, ceramic and preparation method thereof

By adjusting the component content and process steps of the ceramic material, the problem of improving the performance of ceramic materials in the packaging structure is solved, and ceramic materials with high density, high flexural strength and high thermal conductivity are achieved, meeting the multiple needs of the packaging structure.

CN119462105APending Publication Date: 2025-02-18BEIJING 718 YOUSHENG ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411519948.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ceramic materials used in packaging structures are difficult to meet the needs of high density, high flexural strength and high thermal conductivity during the miniaturization and high integration.

Method used

By adjusting the content of components such as alumina, magnesium oxide, calcium carbonate, clay and silica, high-purity alumina ceramic materials are prepared, and the performance of the ceramics is optimized by ball milling, molding and sintering.

Benefits of technology

It has achieved the improvement of high density, flexural strength and thermal conductivity of ceramic materials, and met the packaging structure's needs for mechanical load bearing, airtightness protection and heat dissipation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462105A_ABST
    Figure CN119462105A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a ceramic material for a packaging structure, ceramic and a preparation method thereof, and the ceramic material comprises aluminum oxide and any three of magnesium oxide, calcium carbonate, clay and silicon dioxide; wherein the weight part of the aluminum oxide is between 106 parts and 117 parts; the weight part of the magnesium oxide is between 0.8 part and 2.3 parts, the weight part of the calcium carbonate is between 1.2 parts and 2 parts, the weight part of the clay is between 0.5 part and 1 part, and the weight part of the silicon dioxide is between 1.2 parts and 2.2 parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical materials, and in particular to a ceramic material for packaging structure, ceramic and a preparation method thereof. Background Art

[0002] Ceramics are widely used in packaging technology and packaging structure. With the continuous development of microelectronics technology, packaging is constantly moving towards miniaturization and high integration. The miniaturization and high integration of packaging means that a shell needs to package more chips at the same time within a certain volume. The structure of the shell will inevitably lead to an increasing number of internal cavities, and the side walls of each cavity will become thinner and thinner. This requires the various performances of the ceramics used as the packaging shell to be improved accordingly.

[0003] Therefore, there are still many problems in the practical application of ceramics used for packaging structures that need to be improved. Summary of the invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a ceramic material for packaging structure, which can help obtain high-purity alumina ceramics with high density, high flexural strength and high thermal conductivity by adjusting the content of each component. The ceramic can be used as the shell of the packaging structure to provide mechanical bearing support and airtight protection, and can also be used as a heat sink transition piece to help the chip achieve good heat dissipation effect. This application also provides a preparation method of ceramics for packaging structure and ceramics for packaging structure.

[0005] On one hand, the present application provides a ceramic material for a packaging structure, the ceramic material comprising:

[0006] Alumina, and any three of magnesium oxide, calcium carbonate, clay and silicon dioxide; wherein the weight of the aluminum oxide is between 106 and 117 parts; the weight of the magnesium oxide is between 0.8 and 2.3 parts, the weight of the calcium carbonate is between 1.2 and 2 parts, the weight of the clay is between 0.5 and 1 part, and the weight of the silicon dioxide is between 1.2 and 2.2 parts. In the present application, in the ceramic material provided, the aluminum oxide has a high content, which helps to obtain aluminum oxide ceramics with higher purity. The introduction of other materials and the matching of their content help to improve the flexural strength, density and thermal conductivity of the ceramics obtained based on the ceramic material.

[0007] In any embodiment, the aluminum oxide includes α-aluminum oxide, and the purity is greater than 99.5%. When the aluminum oxide used in the ceramic material is α-aluminum oxide, and the purity is greater than 99.5%, the aluminum oxide ceramic obtained based on the ceramic material can meet the performance requirements for the package shell in the semiconductor integrated circuit. The package shell in the semiconductor integrated circuit has high requirements for materials, and the use of high-purity aluminum oxide can increase the strength of the material.

[0008] In any embodiment, the volume average particle size D50 of the aluminum oxide is in the range of 1.8 μm to 3.5 μm. When the volume average particle size D50 of the aluminum oxide is in the above range, the aluminum oxide ceramic obtained based on the ceramic material can have good mechanical strength and sintered density as well as high thermal conductivity.

[0009] In any embodiment, the ceramic material includes: alumina, calcium carbonate, clay and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset value range, the ceramic obtained on this basis can have a higher density, higher flexural strength and higher thermal conductivity.

[0010] In any embodiment, the ceramic material includes: aluminum oxide, magnesium oxide, calcium carbonate and clay. When the ceramic material includes the above materials and the content of each component is within a preset value range, the ceramic obtained on this basis can have a higher density, higher flexural strength and higher thermal conductivity.

[0011] In any embodiment, the ceramic material includes: aluminum oxide, magnesium oxide, calcium carbonate and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset value range, the ceramic obtained on this basis can have a higher density, higher flexural strength and higher thermal conductivity.

[0012] In any embodiment, the ceramic material includes: alumina, magnesia, clay and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset value range, the ceramic obtained on this basis can have a higher density, higher flexural strength and higher thermal conductivity.

[0013] The second aspect of the present application further provides a method for preparing a ceramic for a packaging structure using the ceramic material of the first aspect of the present application, the preparation method comprising:

[0014] Obtain the ceramic material of the first aspect of the present application;

[0015] placing the material into a ball mill for ball milling to obtain a ceramic slurry;

[0016] forming the ceramic slurry to obtain a green ceramic sheet;

[0017] The green ceramic sheet is sintered to obtain the ceramic.

[0018] In any embodiment, the sintering temperature is between 1500° C. and 1700° C., and optionally, between 1550° C. and 1650° C. It can be understood that the sintering temperature will have a certain influence on the obtained ceramic. When the ceramic material of the present application is used to prepare the ceramic, and the sintering temperature is within the above range, the obtained ceramic can have good flexural strength, high density and high thermal conductivity.

[0019] In any embodiment, the material is placed in a ball mill for ball milling to obtain a ceramic slurry, further comprising:

[0020] Adding solvent, binder and plasticizer into the ball mill;

[0021] The weight of the material is between 95 and 105 parts, the weight of the solvent is between 36 and 44 parts, the weight of the binder is between 5 and 9 parts, and the weight of the plasticizer is between 2 and 5 parts. In this way, when the solvent, binder and plasticizer are added during the ball milling process and their respective amounts are controlled within the above range, it is helpful for the ball milling process to proceed smoothly, and a uniformly mixed ceramic slurry is obtained after the ball milling process is completed.

[0022] In any embodiment, the solvent is selected from at least one of butanone and ethanol, the binder is selected from polyvinyl alcohol, and the plasticizer is selected from dioctyl phthalate. When the above additives are selected from the above materials, it is helpful to adjust the viscosity and other properties of the ceramic slurry and optimize the various properties of the finally obtained ceramic.

[0023] The third aspect of the present application also provides a ceramic for a packaging structure, wherein the ceramic is obtained by using the ceramic material provided by the first aspect of the present application and the preparation method provided by the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A flowchart of a method for preparing ceramics provided in an embodiment of the present application;

[0025] Figure 2 This is a surface photograph of the green ceramic sheet obtained after tape casting and cutting in Example 1 of the present application;

[0026] Figure 3 This is a surface photograph of the ceramic obtained after sintering Example 1 of the present application. DETAILED DESCRIPTION

[0027] Hereinafter, the ceramic material, ceramic and the method for preparing the same of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0028] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0031] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.

[0033] If not otherwise specified, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0034] Alumina ceramic is a ceramic material with aluminum oxide (A12O3) as the main body. With the continuous development of microelectronics technology, packaging is constantly moving towards miniaturization and high integration. The miniaturization and high integration of packaging means that a shell needs to package more chips at the same time within a certain volume. The structure of the shell will inevitably lead to an increasing number of internal cavities, and the side walls of each cavity are getting thinner and thinner. In this way, the various properties of the ceramic used as the packaging shell, such as wear resistance, flexural strength and heat dissipation performance, are also required to be improved accordingly.

[0035] Based on this, the present application proposes a ceramic material for packaging structure, a ceramic and a preparation method thereof, which are described in detail below with reference to the accompanying drawings.

[0036] The present application proposes a ceramic material, which comprises:

[0037] Alumina, and any three of magnesium oxide, calcium carbonate, clay and silicon dioxide;

[0038] Among them, the weight proportion of the aluminum oxide is between 106 and 117 parts (including the endpoint values), for example, 107 to 117 parts, 108 to 117 parts, 109 to 117 parts, 110 to 117 parts, 111 to 117 parts, 112 to 117 parts, 113 to 117 parts, 114 to 117 parts, 115 to 117 parts, 116 to 117 parts, etc.

[0039] The weight portion of the magnesium oxide is between 0.8 and 2.3 parts (including the endpoint values), for example, 0.9 to 2.3 parts, 1.0 to 2.3 parts, 1.1 to 2.3 parts, 1.2 to 2.3 parts, 1.3 to 2.3 parts, 1.4 to 2.3 parts, 1.5 to 2.3 parts, 1.6 to 2.3 parts, 1.7 to 2.3 parts, 1.8 to 2.3 parts, 1.9 to 2.3 parts, 2.0 to 2.3 parts, 2.1 to 2.3 parts, 2.2 to 2.3 parts, etc.

[0040] The weight portion of the calcium carbonate is between 1.2 parts and 2 parts (including the endpoint values), for example, 1.3 parts to 2 parts, 1.4 parts to 2 parts, 1.5 parts to 2 parts, 1.6 parts to 2 parts, 1.7 parts to 2 parts, 1.8 parts to 2 parts, 1.9 parts to 2 parts, etc.

[0041] The weight portion of the clay is between 0.5 and 1 parts (including the end points), for example, 0.6 to 1 parts, 0.7 to 1 parts, 0.8 to 1 parts, 0.9 to 1 parts, etc.

[0042] The weight proportion of the silicon dioxide is between 1.2 and 2.2 parts (including the endpoint values), for example, 1.3 to 2.2 parts, 1.4 to 2.2 parts, 1.5 to 2.2 parts, 1.6 to 2.2 parts, 1.7 to 2.2 parts, 1.8 to 2.2 parts, 1.9 to 2.2 parts, 2.0 to 2.2 parts, 2.1 to 2.2 parts, etc.

[0043] In the present application, the ceramic material provided has a high content of aluminum oxide, which helps to obtain aluminum oxide ceramics with higher purity. The introduction of other materials and the matching of their contents help to improve the flexural strength, density and thermal conductivity of the ceramics obtained based on the ceramic material.

[0044] In some embodiments, aluminum oxide, magnesium oxide, calcium carbonate, and silicon dioxide may all be powder materials.

[0045] In some embodiments, the alumina includes α-alumina with a purity greater than 99.5%.

[0046] It can be understood that when the aluminum oxide used in the ceramic material is α-aluminum oxide and its purity is greater than 99.5%, the ceramic obtained based on this ceramic material can meet the performance requirements for the packaging shell in the semiconductor integrated circuit. The packaging shell in the semiconductor integrated circuit has high requirements for materials. The use of high-purity aluminum oxide can increase the strength of the material.

[0047] In some embodiments, the volume average particle size D50 of the aluminum oxide is between 1.8 μm and 3.5 μm (including endpoint values), for example, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, etc.

[0048] It can be understood that when the volume average particle size D50 of alumina is within the above range, the alumina ceramics obtained based on the ceramic material can have good mechanical strength and sintered density as well as higher thermal conductivity.

[0049] In some embodiments, the ceramic material includes: alumina, calcium carbonate, clay and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset numerical range, since calcium carbonate, clay and silicon dioxide form a suitable sintering aid under a suitable ratio, they form a liquid phase with alumina at a high temperature, which helps to accelerate the transmission of substances (i.e., the materials used to form ceramics), fill pores, and increase the density of ceramics. The ceramics obtained on this basis can have a higher density, higher flexural strength and higher thermal conductivity.

[0050] In some embodiments, the ceramic material includes: aluminum oxide, magnesium oxide, calcium carbonate and clay. When the ceramic material includes the above materials and the content of each component is within a preset value range, due to the theory roughly the same as the previous embodiment, when magnesium oxide, calcium carbonate and clay are in a suitable ratio, the ceramic obtained on this basis can also have good density performance, good flexural strength and good thermal conductivity.

[0051] In some embodiments, the ceramic material includes: aluminum oxide, magnesium oxide, calcium carbonate and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset value range, due to the theory roughly the same as the previous embodiment, when magnesium oxide, calcium carbonate and silicon dioxide are in a suitable ratio, the ceramic obtained on this basis can have good density performance, good flexural strength and good thermal conductivity.

[0052] In some embodiments, the ceramic material includes: aluminum oxide, magnesium oxide, clay and silicon dioxide. When the ceramic material includes the above materials and the content of each component is within a preset value range, due to the theory roughly the same as the previous embodiment, when magnesium oxide, clay and silicon dioxide are in a suitable ratio, the ceramic obtained on this basis can have good high density performance, good flexural strength and good thermal conductivity.

[0053] The second aspect of the embodiment of the present application also provides a method for preparing a ceramic for a packaging structure, such as Figure 1 As shown, the preparation method comprises the following steps:

[0054] Step S101: Obtain the ceramic material provided by any of the above embodiments of the present application;

[0055] Step S102: placing the material into a ball mill for ball milling to obtain a ceramic slurry;

[0056] Step S103: forming the ceramic slurry to obtain a green ceramic sheet;

[0057] Step S104: sintering the green ceramic sheet to obtain ceramics.

[0058] First, weigh each component material according to a certain ratio, and the ceramic materials include Al2O3, MgO, CaCO3, clay, and SiO2.

[0059] Next, weighed Al2O3 and the following materials: any three of clay, CaCO3, MgO and SiO2 (can be selected according to the specific embodiment) are added into a ball mill, and then a solvent and a dispersant are added for primary ball milling. After a period of ball milling, a solvent, a binder and a plasticizer are added for secondary ball milling.

[0060] In some embodiments, the material is placed in a ball mill for ball milling to obtain a ceramic slurry, further comprising:

[0061] Adding solvent, binder and plasticizer into the ball mill;

[0062] Among them, the weight of the material is between 95 parts and 105 parts (including the endpoint value), the weight of the solvent is between 36 parts and 44 parts (including the endpoint value), the weight of the binder is between 5 parts and 9 parts (including the endpoint value), and the weight of the plasticizer is between 2 parts and 5 parts (including the endpoint value).

[0063] Thus, when the solvent, binder and plasticizer are added during the ball milling process and their respective amounts are controlled within the above range, the ball milling process can be smoothly carried out, and a uniformly mixed ceramic slurry can be obtained after the ball milling process is completed.

[0064] In some embodiments, the values ​​of the material, solvent, binder and plasticizer can be endpoint values, but are not limited thereto, and can also be any values ​​between the endpoint values, for example: the weight of the material can be 96 parts, 97 parts, 98 parts, 99 parts, 100 parts, 101 parts, 102 parts, 103 parts, 104 parts, etc. The weight of the solvent can be 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, etc. The weight of the binder can be 6 parts, 7 parts, 8 parts, etc. The weight of the plasticizer can be 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc.

[0065] In some embodiments, the solvent is selected from at least one of butanone and ethanol, the binder is selected from polyvinyl alcohol, and the plasticizer is selected from dioctyl phthalate. When the above additives are selected from the above materials, it is helpful to adjust the viscosity and other properties of the ceramic slurry and optimize the various properties of the ceramic finally obtained.

[0066] It is understandable that adding certain additives to ceramic materials can help mix ceramic materials and optimize the properties of the prepared ceramics. Among them, the viscosity of the ceramic slurry can be adjusted by controlling the proportion of the solvent; adding a suitable amount of binder to connect the components together; adding a suitable amount of plasticizer to increase the plasticity of the ceramic, that is, additives can improve certain properties of the ceramic.

[0067] In some embodiments, the time range of a ball milling can be between 18h and 26h (including the endpoint values), for example, between 18h and 20h (including the endpoint values), for example, 19h, etc., between 20h and 24h (including the endpoint values), for example, 21h, 22h, or 23h, etc.; or between 24h and 26h (including the endpoint values), for example, 25h, etc.

[0068] In some embodiments, the time range of the secondary ball milling can be between 18h and 26h (including the endpoint values), for example, between 18h and 20h (including the endpoint values), for example, 19h, etc., between 20h and 24h (including the endpoint values), for example, 21h, 22h, or 23h, etc.; or between 24h and 26h (including the endpoint values), for example, 25h, etc.

[0069] The ball milling step is performed using a ball mill, and when the ball milling time is within the above range, it is helpful to promote uniform mixing between the materials.

[0070] In some embodiments, after ball milling and before obtaining the green ceramic sheet, the preparation method further comprises vacuum degassing, that is, after the secondary ball milling, the slurry is vacuum degassed to obtain the ceramic slurry.

[0071] It can be understood that the execution of the vacuum degassing step can effectively eliminate bubbles in the ceramic slurry, make the slurry more stable, and improve the stability and quality of the final ceramics.

[0072] In some embodiments, the degassing time can range from 20 min to 50 min (including endpoint values), for example, between 20 min and 50 min (including endpoint values), for example, between 20 min and 40 min (including endpoint values), such as 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, etc., between 40 min and 50 min (including endpoint values), such as 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min, etc.

[0073] Then, the ceramic slurry obtained in the previous step is tape-casted. Specifically, the ceramic slurry obtained in the previous step can be tape-casted on a tape-casting machine to obtain a green ceramic tape, and then the green ceramic tape is placed on a slicer for slicing to obtain Figure 2 From the green porcelain sheet of the required size shown (corresponding to Example 1 of the present application), it can be seen that no bubbles, cracks, dirt, etc. are generated in the green porcelain sheet obtained by the preparation method provided in the example of the present application.

[0074] Next, in some embodiments, after obtaining the green porcelain sheets, the green porcelain sheets may be further cut into required sizes through lamination and hot cutting to obtain green porcelain blocks.

[0075] Next, the green ceramic sheet (or green ceramic block) is placed in a vacuum sintering furnace for debinding and sintering to remove organic matter from the green ceramic sheet (or green ceramic block) and sinter to obtain a Figure 3 The ceramic shown (corresponding to Example 1 of the present application) can be obtained Figure 3 The high-purity alumina ceramic shown (corresponding to Example 1 of the present application).

[0076] In an embodiment of the present application, by adopting the ceramic material provided in the first aspect of the present application and the preparation method provided in the second aspect of the present application, the content of aluminum oxide in the obtained aluminum oxide ceramic is about 96%, for example, greater than 96%.

[0077] In some embodiments, the sintering temperature is between 1500°C and 1700°C (including the endpoint value), for example, between 1500°C and 1550°C (including the endpoint value), between 1550°C and 1650°C (including the endpoint value), between 1650°C and 1700°C (including the endpoint value). Optionally, the sintering temperature can be between 1550°C and 1650°C (including the endpoint value).

[0078] Here, the sintering temperature can be either end point value or any value between the two end points, for example, it can be 1500°C, 1520°C, 1550°C, 1580°C, 1600°C, 1620°C, 1650°C, 1680°C or 1700°C, etc.

[0079] In some embodiments, the sintering holding time ranges from 1 to 3 hours (including endpoint values), for example: 1.5 hours, 2 hours, 2.5 hours, etc.

[0080] In some embodiments, after obtaining the ceramic, the obtained ceramic may be subjected to density measurement and performance test, wherein the density measurement may be performed using an electronic density meter, for example. The performance test may be performed using a universal material testing machine to test the flexural strength of the ceramic and a laser thermal conductivity tester to test the thermal conductivity of the ceramic.

[0081] The third aspect of the embodiment of the present application further provides a ceramic for a packaging structure, wherein the ceramic is obtained by using the ceramic material provided by the first aspect of the present application and the preparation method provided by the second aspect of the present application.

[0082] It is understandable that alumina ceramics used in electronic packaging shells can not only provide mechanical support and airtight protection for electronic components and their interconnections, but also serve as heat sink transition pieces to dissipate heat from chips, so they need to have excellent thermal conductivity. According to the alumina content, additives and uses, alumina ceramics are divided into white porcelain and black porcelain. White porcelain has a relatively high purity and good wear resistance, and is widely used in ceramic substrates such as thick film circuits, thin film circuits, and multi-layer HTCC circuit boards.

[0083] However, the premise of using ceramics is good density, so it is necessary to prepare a high-purity alumina white porcelain with high flexural strength, high thermal conductivity and high density for packaging shells.

[0084] In the present application, the ceramic obtained by the ceramic material and preparation method provided in the embodiments of the present application can be: high-purity alumina white porcelain with good compactness, high flexural strength, high thermal conductivity and high density. The white porcelain has relatively high purity and good wear resistance, and is widely used in the field of ceramic substrates such as thick film circuits, thin film circuits, and multilayer HTCC circuit boards (high temperature co-fired ceramics (HTCC, High Temperature Co-fired Ceramics) substrates). In some specific embodiments, it can be used as a packaging shell in a packaging structure.

[0085] Example

[0086] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0087] Example

[0088] Preparation of ceramics

[0089] Example 1

[0090] (1) Weighing

[0091] Alumina ceramics are prepared from the following components in mass percentage: 112 parts of alumina powder (the alumina powder is α-alumina, with a purity greater than 99.5% and a particle size of 3 μm), 1.5 parts of CaCO3 powder, 0.5 parts of clay, and 2 parts of SiO2 powder. The ceramic material is obtained by weighing the material components according to the above ratio and set aside.

[0092] (2) Ball milling

[0093] The weighed ceramic material is added into the ball mill, and then the solvent, dispersant and defoaming agent are added for the first ball milling, and the first ball milling time is 20 hours. Then the binder and plasticizer are added for the second ball milling, and the second ball milling time is 20 hours.

[0094] (3) Vacuum degassing

[0095] The ball-milled material was vacuum degassed for 40 minutes using a vacuum degassing machine to obtain a ceramic slurry.

[0096] (4) Tape casting

[0097] The ceramic slurry obtained in step (3) is tape-casted on a tape-casting machine to obtain a green ceramic tape, which is then placed on a slicer for slicing to obtain green ceramic sheets of a desired size;

[0098] (5) Lamination

[0099] (6) Lamination

[0100] (7) Eager

[0101] Cut into raw porcelain blocks of required size.

[0102] (8) Sintering

[0103] The green porcelain block is placed in a vacuum sintering furnace for debinding and sintering to remove organic matter in the green porcelain block and sinter it into shape. The sintering temperature is 1560℃ and the holding time is 2h.

[0104] Embodiment 2-4

[0105] The ceramics of each embodiment were prepared in a similar manner to that of embodiment 1. The weights of the materials used in each specific embodiment are shown in Table 1. In these embodiments, the settings of the specific parameters involved in each step are shown in Table 1.

[0106] Comparative Example 1

[0107] The ceramic of the comparative example was prepared in a similar manner to that of Example 1. The specific weights of the materials used are shown in Table 1. The specific parameter settings involved in each step are shown in Table 1.

[0108] Density measurement and performance testing

[0109] The following measurements and tests were performed on the ceramics obtained in the above examples and comparative examples.

[0110] 1. Density measurement

[0111] The density of the ceramics prepared in Examples 1-4 and Comparative Example 1 was measured using an electronic density meter. Please refer to Table 1 for specific measurement results.

[0112] Performance Testing

[0113] 2. Flexural strength test

[0114] The flexural strength of ceramics was measured according to GB / T 9341-2008 standard. The ceramics prepared in Examples 1-4 and Comparative Example 1 were tested for flexural strength using a universal material testing machine. Please refer to Table 1 for specific test results.

[0115] 3. Thermal conductivity test

[0116] The thermal conductivity of the ceramics was measured according to GB / T 5598-2015 standard. The ceramics prepared in Examples 1-4 and Comparative Example 1 were tested for thermal conductivity using a laser thermal conductivity meter. Please refer to Table 1 for specific test results.

[0117] The measurement results of item 1 and the test results of items 2-3 of the ceramics prepared by the above embodiments and comparative examples are shown in Table 1 below:

[0118]

[0119] It can be seen from Table 1 above that, relative to Comparative Example 1, the ceramics obtained in Examples 1-4 have achieved excellent results in density, flexural strength and thermal conductivity. That is to say, compared with Comparative Example 1, the ceramics obtained in each example have better density performance, better flexural strength and better thermal conductivity.

[0120] In Example 1, calcium carbonate, clay and silicon dioxide have a suitable ratio to form a suitable sintering aid, so that it forms a liquid phase with alumina at a high temperature, which helps to accelerate the transmission of substances, fill the pores, reduce the amount of internal pores, and increase the density of the ceramic. The density is improved, the strength of the ceramic grain boundary is increased, and the flexural strength and other properties are improved.

[0121] In Example 2, when the components are changed, since magnesium oxide, calcium carbonate and clay have a suitable ratio, the obtained ceramic can still obtain good density, good flexural strength and good thermal conductivity compared with Comparative Example 1.

[0122] In Example 3, when the components are changed, since magnesium oxide, calcium carbonate and silicon dioxide have a suitable ratio, the obtained ceramic can also obtain good density, good flexural strength and good thermal conductivity compared with Comparative Example 1.

[0123] In Example 4, when the components are changed, since magnesium oxide, clay and silicon dioxide have a suitable ratio, the obtained ceramic can also obtain good density, good flexural strength and good thermal conductivity compared with Comparative Example 1.

[0124] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A ceramic material for packaging structure, characterized in that: include: Alumina, and any three of magnesium oxide, calcium carbonate, clay and silicon dioxide; wherein the weight portion of the aluminum oxide is between 106 and 117 parts; the weight portion of the magnesium oxide is between 0.8 and 2.3 parts, the weight portion of the calcium carbonate is between 1.2 and 2 parts, the weight portion of the clay is between 0.5 and 1 part, and the weight portion of the silicon dioxide is between 1.2 and 2.2 parts.

2. The material according to claim 1, characterized in that The alumina comprises α-alumina, and the purity thereof is greater than 99.5%.

3. The material according to any one of claims 1 to 2, characterized in that The volume average particle size D50 of the aluminum oxide is in the range of 1.8 μm to 3.5 μm.

4. The material according to any one of claims 1 to 3, characterized in that The materials include: alumina, calcium carbonate, clay and silicon dioxide.

5. The material according to any one of claims 1 to 4, characterized in that The materials include: aluminum oxide, magnesium oxide, calcium carbonate and clay.

6. The material according to any one of claims 1 to 5, characterized in that The materials include: aluminum oxide, magnesium oxide, calcium carbonate and silicon dioxide.

7. The material according to any one of claims 1 to 6, characterized in that The materials include: alumina, magnesia, clay and silicon dioxide.

8. A method for preparing a ceramic for packaging structure, characterized in that: The preparation method comprises: Obtaining the ceramic material according to any one of claims 1 to 7; placing the material into a ball mill for ball milling to obtain a ceramic slurry; forming the ceramic slurry to obtain a green ceramic sheet; The green ceramic sheet is sintered to obtain the ceramic.

9. The preparation method according to claim 8, characterized in that: The sintering temperature is between 1500°C and 1700°C, and optionally, between 1550°C and 1650°C.

10. The preparation method according to any one of claims 8 to 9, characterized in that: The material is put into a ball mill for ball milling to obtain a ceramic slurry, and further comprising: Adding solvent, binder and plasticizer into the ball mill; Among them, the weight of the material is between 95 parts and 105 parts, the weight of the solvent is between 36 parts and 44 parts, the weight of the binder is between 5 parts and 9 parts, and the weight of the plasticizer is between 2 parts and 5 parts.

11. The preparation method according to any one of claims 8 to 10, characterized in that: The solvent is selected from at least one of butanone and ethanol, the binder is selected from polyvinyl alcohol, and the plasticizer is selected from dioctyl phthalate.

12. A ceramic for packaging structure, characterized in that: The ceramic is obtained by the preparation method described in any one of claims 8 to 11 using the material described in any one of claims 1 to 7.